The participating citizen : a biography of Alfred Schutz - Barber, Michael D., 1949- (State University of New York Press, 2004)
An in-depth biography of the philosopher who brought phenomenology to the social sciences.
Keywords: Schutz, Alfred, -- 1899-1959.; Schutz, Alfred, -- 1899-1959; Sociologists -- Austria -- Biography.; Phenomenological sociology.; Sociologues -- Autriche -- Biographies.; Sociologie phénoménologique.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists.; SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Anthropology -- General.; Phenomenological sociology; Sociologists; Austria; Biographies; Biographies.